2019
DOI: 10.1002/humu.23803
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐associated missense variants in ZBTB18 disrupt DNA binding and impair the development of neurons within the embryonic cerebral cortex

Abstract: The activities of DNA‐binding transcription factors, such as the multi‐zinc‐finger protein ZBTB18 (also known as RP58, or ZNF238), are essential to coordinate mammalian neurodevelopment, including the birth and radial migration of newborn neurons within the fetal brain. In humans, the majority of disease‐associated missense mutations in ZBTB18 lie within the DNA‐binding zinc‐finger domain and are associated with brain developmental disorder, yet the molecular mechanisms explaining their role in disease remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(61 citation statements)
references
References 47 publications
0
60
1
Order By: Relevance
“…Firefly luciferase expression constructs were utilized for luciferase assays (Four separate Rnd2 3′-enhancer constructs comprising E1 and E2 motifs; E1 mut and E2 motifs; E1 and E2 mut motifs; and E1 mut and E2 mut motifs were previously reported (Hemming et al, 2019;Heng et al, 2008Heng et al, , 2013 undertaken with this previously reported pIDT-AMP-WT construct.…”
Section: Dna Constructs and Cloningmentioning
confidence: 99%
See 4 more Smart Citations
“…Firefly luciferase expression constructs were utilized for luciferase assays (Four separate Rnd2 3′-enhancer constructs comprising E1 and E2 motifs; E1 mut and E2 motifs; E1 and E2 mut motifs; and E1 mut and E2 mut motifs were previously reported (Hemming et al, 2019;Heng et al, 2008Heng et al, , 2013 undertaken with this previously reported pIDT-AMP-WT construct.…”
Section: Dna Constructs and Cloningmentioning
confidence: 99%
“…The ZBTB18 gene encodes a polypeptide comprising an N-terminal BTB domain for protein-protein interaction, as well as four Cys2-His2-like (C2H2) ZFs at its C terminus for DNA binding to a consensus DNA motif, defined as 5′-[AC]ACANCTG [GT][AC]-3′ (Aoki et al, 1998;Hirai et al, 2012). Recently, we and others have reported that disease-associated ZBTB18 missense variants cluster within the C-terminal ZF DNA-binding domain (Farwell et al, 2015;Hemming et al, 2019;Landrum et al, 2018;Rauch et al, 2012;van der Schoot et al, 2018). Furthermore, we characterized two disease-associated ZBTB18 missense variants (N461S (Farwell et al, 2015) and R495G (Rauch et al, 2012)) and found that each disrupted its DNA-binding specificity, transcriptional regulatory function and neurodevelopmental signaling capacity in different ways (Hemming et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations